Empowerment among generations. (November 2017) - Singh, Usha; Weimar, Daniel
The study investigates differences in people's attitudes towards empowerment among generations and other demographic variables as there are only few insights available so far. Therefore, a combination of a hierarchical and a non-hierarchical cluster analysis is used, leading to two clusters termed 'empowered employees' and 'less empowered employees'. Chi-square tests are applied to investigate the differences in the demographic variables among the clusters. Furthermore, a discriminant analysis is carried out to check the segmentation strength and the consistency of the clusters. Additionally, multivariate ordinary least squares (OLS) and logit estimations are used as a robustness check. Results indicate that people from Generation X and the Post-war Generation are more likely to tend towards empowerment than Baby Boomers.